Customer’s expectation, perception and satisfaction with service quality of a fitness center in Malaysia - Yusof, Aminuddin; Joseph, Jacklyn; M. Shah, Parilah (AkiNik Publications, 2017)
This study examined customer’s expectation, perception and satisfaction with service quality of a fitness centre in Malaysia. The study also investigated whether there are differences in satisfaction with service quality based on gender and ethnicity of fitness centre customers. Data were collected using questionnaires distributed to all members of one fitness centre (N =248). The results showed demographic variables not important in evaluating service quality. On the other hand, empathy and assurance were found to be the two most important dimensions for customer’s satisfaction with fitness centers in Malaysia. However, all dimensions of service quality were discovered to have negative means indicating customers are dissatisfied will all aspects of service quality at the fitness centre. The results were discussed based on the gap model. Implications of the study for fitness centers were also provided in the paper.